2021
DOI: 10.1080/10428194.2021.1992623
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence and prognosis of hyponatraemia in non-Hodgkin lymphoma-associated hemophagocytic lymphohistiocytosis

Abstract: Background:Non-Hodgkin lymphoma associated hemophagocytic lymphohistiocytosis (NHL-HLH) in adult secondary HLH (sHLH) is a common and universally highly lethal critical disorder. Hyponatraemia is the most common electrolyte disorder in the critical illness setting and acts as a negative prognostic factor.The aim of our study was to evaluate the prognostic role of hyponatraemia among patients with NHL-HLH.Methods: This retrospective study enrolled 153 newly diagnosed adult NHL-HLH patients, which were divided i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…In the study by Yao et al, which included 104 non-Hodgkin lymphomaassociated HLH, age, IPI, platelet count, and the NK/T lymphoma subtype were independent risk factors for non-Hodgkin lymphoma-associated HLH (23). Other factors, including poor performance status and hyponatremia, were identi ed as negative prognostic factors for lymphoma-associated HLH (4,24). Li et al also found that a higher EBV load was a negative predictor in B-NHL-associated HLH, however, this study was restricted to B-NHL and only included 31 cases (4).…”
Section: Discussionmentioning
confidence: 99%
“…In the study by Yao et al, which included 104 non-Hodgkin lymphomaassociated HLH, age, IPI, platelet count, and the NK/T lymphoma subtype were independent risk factors for non-Hodgkin lymphoma-associated HLH (23). Other factors, including poor performance status and hyponatremia, were identi ed as negative prognostic factors for lymphoma-associated HLH (4,24). Li et al also found that a higher EBV load was a negative predictor in B-NHL-associated HLH, however, this study was restricted to B-NHL and only included 31 cases (4).…”
Section: Discussionmentioning
confidence: 99%